Β‐CsB9O14: A Triple‐Layered Borate with Edge‐Sharing BO4 Tetrahedra Exhibiting a Short Cutoff Edge and a Large Birefringence. Issue 50 (10th July 2019) - Han, Shujuan; Huang, Chunmei; Tudi, Abudukadi; Hu, Shuaishuai; Yang, Zhihua; Pan, Shilie
Abstract: The first triple‐layered borate with edge‐sharing BO4 tetrahedra, β‐CsB9 O14 was obtained under vacuum‐sealed condition. It represents a new structure type and enriches the structural diversity of borates. Moreover, β‐CsB9 O14 exhibits a short UV cutoff edge and a large birefringence, indicating that it could be regarded as a DUV birefringent crystal. Abstract : Triple whammy : β‐CsB9 O14 is the first triple‐layered borate with edge‐sharing BO4 tetrahedra, which represents a new structure type of borates, enriching the diversity of these materials.